Aesthetics of Employing Folklore Heritage in Fashion Design Techniques: Iraqi Designer Hana Sadiq as a Model (Al-Academy, 2026)
This study aims to explore the aesthetics of Iraqi folk heritage in the fashion designs of Hana Sadiq, with the objective of analyzing how traditional cultural elements can be integrated into contemporary design practices. The research adopted an analytical–experimental methodology, focusing on six selected models from Sadiq’s works, which were assessed across three main dimensions: the aesthetic dimension (colors, shapes, calligraphy, motifs), the folk heritage dimension (identity, cultural symbols, environment, civilization), and the technical execution dimension (hand embroidery, digital printing, fabrics, cuts). The findings revealed statistically significant differences among the designs, with models such as The Royal Tribal Abaya and The Baghdadi Style standing out for their ability to merge authenticity with innovation, while other models reflected subtler levels of heritage expression. Based on these results, the study recommends integrating folk heritage more widely into fashion education curricula, encouraging designers to combine traditional craftsmanship with modern technology, supporting cultural institutions to promote heritage-based fashion globally, and conducting comparative studies with international designers to enhance cross-cultural dialogue